Addition of selenium to carica papaya linn pulp extract enhances dermal wound healing activity - Abdulrazaq, Nafiu Bidemi; Akram, Haris; Bero, Dinie Najwa; Yusoff, Mohammed; Abd Malik, Izzati; Rahman, Mohammad Tariqur (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2013)
Purpose: To investigate the combined effect of Carica papaya extract and mineral elements wound healing. Methods: Phosphate-buffered saline (PBS) and water extracts of unripe Carica papaya. papaya were analyzed for mineral element composition (Ca, calcium; Mg, magnesium; Na, sodium; Fe, iron; Mn, manganese; Zn, zinc; Ag, silver; and Se, selenium) using a microwave-assisted digestion procedure. Atomic absorption spectrophotometry was used for the analysis of the elements. Phytochemical analysis was conducted using standard protocols. Mice weighing 25 - 30 g were anesthetized, shaved and inflicted with wound at the dorsal region using a biopsy punch. The mice were treated topically twice daily with or without 5 mg/ml PBS or water extracts containing 100 or 200 μM Zn2+ or 1.0 or 0.5 μg/g Se2+. The standard (positive control) group was treated with solcoseryl and the negative control with deionised H2O. Wound area was monitored with a camera and evaluated by software. Results: PBS extract formulated with Se2+. (0.5 or 1.0 mg/g) took approximately 9 days for complete wound healing while negative control took 14 days and other treatment groups least 10 days. PBS extract contained 9 % protein but no tannin while water extract contained 0.58 % protein and tannins. Calcium (137.98 mg/100 g extract) constituted the most abundant macro-element while Se (32.14 mg/100 g extract) was the most abundant microelement in C. papaya pulp. Conclusion: Addition of selenium to C. papaya extracts augments the wound healing activity of the extracts.